The Effect of ESG Disclosure on Company Value with Profitability as a Moderation Variable - Yulius Paul Pian; Sari Rusmita; Umiaty Hamzani (Indonesian Journal of Business Analytics, 2026)
This study aims to examine the influence of Environmental, Social, and Governance (ESG) disclosure on Company Value proxied using Tobin's Q, as well as to test the role of profitability as a moderation variable in companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. The study used an explanatory quantitative approach with panel data consisting of 117 companies during the observation period, resulting in 574 observations (unbalanced panels). The model selection was carried out through the Chow Test, the Hausman Test, and the Lagrange Multiplier (LM) Test. The test results showed that the Chow Test (p=0.0000), the Hausman Test (p=0.0407), and the LM Test (p=0.0000) directed the best model to the Fixed Effect Model (FEM). The results of the estimate show that ESG has a coefficient of −0.044 (p=0.823) so that it does not have a significant effect on the Company's Value. The ESG×ROA moderation variable also showed a coefficient of −0.161 (p=0.856) so it was not proven to moderate the relationship between ESG and Company Value. However, the model is simultaneously significant with an F-statistic value of 8.239 and Prob(F-statistic)=0.0000, so the model is considered feasible to use. An Adjusted R² value of 0.599 indicates that the model is able to explain 59.9% of Tobin's Q variations. These results are in line with Patima et al. (2024) which found that environmental disclosure did not have a significant effect on the company's value in the basic materials sector on the IDX.